Insulating materials. Industrial, rigid, moulded, laminated tubes and rods of rectangular and hexagonal cross-section based on thermosetting resins for electrical purposes. Definitions, designations and general requirements Part 1, (14th August 2002) - British Standards Institution,
No abstract available